Docetaxel chemotherapy in metastatic castration-resistant prostate cancer: cost of care in Medicare and commercial populations. (3rd June 2017) - Armstrong, A.; Bui, C.; Fitch, K.; Sawhney, T. Goss; Brown, B.; Flanders, S.; Balk, M.; Deangelis, J.; Chambers, J.
Abstract: Objective: To estimate the healthcare costs and characteristics of docetaxel chemotherapy episodes of care for men with metastatic castration-resistant prostate cancer (mCRPC). Methods: This study used the Medicare 5% sample and MarketScan Commercial (2010–2013) claims data sets to identify men with mCRPC and initial episodes of docetaxel treatment. Docetaxel episodes included docetaxel claim costs from the first claim until 30 days after the last claim, with earlier termination for death, insurance disenrollment, or the end of a 24-month look-forward period from initial docetaxel index date. Docetaxel drug claim costs were adjusted for 2011 generic docetaxel introduction, while other costs were adjusted to 2015 values using the national average annual unit cost increase. Results: This study identified 281 Medicare-insured and 155 commercially insured men, with 325 and 172 docetaxel episodes, respectively. The average number of cycles (unique docetaxel infusion days) per episode was 6.9 for Medicare and 6.3 for commercial cohorts. The average cost per episode was 28, 792 for Medicare and 67, 958 for commercial cohorts, with docetaxel drug costs contributing 2, 588 and 13, 169 per episode, respectively. The average cost per episode on docetaxel infusion days was 8, 577 (30%) for Medicare and 28, 412 (42%) for commercial. Non-docetaxel infusion day costs included 7, 074 (25%) for infused or injected drugs for Medicare, 10, 838 (16%) for commercial cohorts, and 6, 875 (24%) and 9, 324 (14%) for inpatient admissions, respectively. Limitations: The applicability is only to the metastatic castration-resistance clinical setting, rather than the metastatic hormone-sensitive setting, and the lack of data on the cost effectiveness of different sequencing strategies of a range of systemic therapies including enzalutamide, abiraterone, radium-223, and taxane chemotherapy. Conclusion: The majority of docetaxel episode costs in Medicare and commercial mCRPC populations were non-docetaxel drug costs. Future research should evaluate the total cost of care in mCPRC.